PENYULUHAN HUKUM TENTANG MENINGKATKAN PEMAHAMAN DAN KESADARAN HUKUM MASYARAKAT DI KECAMATAN TEBET KOTA JAKARTA SELATAN - Anggriani, Jum; Harlina, Indah; Samosir, Tetti; Finadi, Andreas Sapta (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2024)
The level of legal awareness and citizens' obedience to the law can show the progress of a country. The life of society and the country will be more orderly if the legal awareness and legal obedience of the population is higher. These factors of legal awareness and legal compliance play an important role in legal progress; The level of public legal awareness is negatively correlated with the level of legal compliance, and conversely, the level of public legal awareness is negatively correlated with the level of legal compliance. Public legal awareness will create an effective law enforcement environment, which can provide a sense of justice, create legal certainty in society, and provide justice. The aim of legal counseling is to increase public legal awareness through legal consultations, collaborating with local legal consultants, and disseminating information about law in Tebet District, South Jakarta City. The aim of legal counseling is to increase public legal awareness in Tebet District, South Jakarta City. Keywords:law, awareness, counseling